Choosing the Right Kind of Accreditation for a Business School: A Comparison between AACSB, ACBSP, and IACBE - Babu George (University Babes-Bolyai, 2018)
This paper offers a comparison of the accreditation standards of three CHEA and US Department of Education recognized business school program accreditation agencies - AACSB, ACBSP, and IACBE. It also discusses the relative challenges and benefits of achieving accreditation by these agencies. While the choice for business schools is often not very clear and is a long drawn negotiated process involving different interest groups, this paper will nevertheless offer some basis of comparison among the accreditation agencies. The author draws heavily from his own personal experiences leading accreditation efforts in various US based and international b-schools and proposes the merits and demerits of different alternatives.